Mechanistic dissection of premature translation termination induced by acidic residues-enriched nascent peptide - Yuhei Chadani; Takashi Kanamori; Tatsuya Niwa; Kazuya Ichihara; Keiichi I. Nakayama; Akinobu Matsumoto; Hideki Taguchi (Cell Reports, 2023)
Summary: Ribosomes polymerize nascent peptides through repeated inter-subunit rearrangements between the classic and hybrid states. The peptidyl-tRNA, the intermediate species during translation elongation, stabilizes the translating ribosome to ensure robust continuity of elongation. However, the translation of acidic residue-rich sequences destabilizes the ribosome, leading to a stochastic premature translation cessation termed intrinsic ribosome destabilization (IRD), which is still ill-defined. Here, we dissect the molecular mechanisms underlying IRD in Escherichia coli. Reconstitution of the IRD event reveals that (1) the prolonged ribosome stalling enhances IRD-mediated translation discontinuation, (2) IRD depends on temperature, (3) the destabilized 70S ribosome complex is not necessarily split, and (4) the destabilized ribosome is subjected to peptidyl-tRNA hydrolase-mediated hydrolysis of the peptidyl-tRNA without subunit splitting or recycling factors-mediated subunit splitting. Collectively, our data indicate that the translation of acidic-rich sequences alters the conformation of the 70S ribosome to an aberrant state that allows the noncanonical premature termination.